Improvement of yield and other traits of extra early maize under stress and nonstress environments - Badu-Apraku, Baffour; Fakorede, M.A.B.; Lum, A.F.; Akinwale, R. (2009)
Striga, drought, and low soil fertility constrain maize (Zea mays L.) productivity in West and Central Africa. Two Striga-resistant extra-early populations, TZEE-W Pop STR C0 (white) and TZEE-Y Pop STR C0 (yellow) were evaluated in field trials in Nigeria, from 2005 to 2007 to assess progress in improvements for grain yield, Striga resistance, and other traits when Striga-free, Striga-infested, and under low- and high-N. Under Striga infestation, yield gain from C0 to C4 was 136 kg ha−1 for the yellow population and 71 kg ha−1 cycle−1 for the white. The yield gain in advanced cycles of selection in the yellow was associated with decreases in Striga emergence at 8 and 10 weeks after planting (WAP) and Striga damage at 8 WAP while that of the white was accompanied by increased days to silking and ears per plant as well as a decrease in Striga emergence at 8 WAP. Under Striga-free conditions, yield gain from C0 to C4 was 164 kg ha−1cycle−1 for the white and 221 kg ha−1 cycle−1 for the yellow. The yield gain in advanced cycles of selection was more pronounced under high-N (157 kg ha−1 cycle−1) than low-N (144 kg ha−1cycle−1) in the yellow, and higher under low-N than high-N in the white. Selection in the yellow was accompanied by increased days to anthesis and silking, plant and ear heights under low-N and increased days to silking under high-N. In the white, selection induced increased days to anthesis, ear height, and decreased anthesis-silking interval.